University Climate Curriculum Technical Writeshop for the RUFORUM Curriculum Platform - Grossi, Amanda; Dinku, Tufa; Hansen, James; Nakayiwa, Florence; Mwanjalolo, Majaliwa; Kibe, Anthony M.; Nakyobe, Judith; Amitu, David Martin; Nimusiima, Alex; Wasonga, Oliver Vivian (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Tackling the climate crisis means equipping the youth with the knowledge and skills they need to manage climate risk. Universities across Africa have an enormous role to play towards this end. By equipping the next generation of researchers, policymakers, and leaders with the knowledge and skills they need to build resilient societies, education systems represent an important avenue for sustained capacity building beyond project life cycles. Technological innovations and in particular e-Learning platforms such as the RUFORUM Curriculum Platform (Moodle) have been and will continue to be instrumental in expanding access to such information and advancing skills to meet the climate challenge.